The Mechanisms of Symbolic Violence against Learners with Disabilities in an Inclusive Primary School in View of Pierre Bourdieu's Theory - Nur Mashlichah Ilma; Kemil Wachidah (Mimbar Ilmu, 2025)
Education, particularly inclusive education, should uphold equality and respect for diversity. However, symbolic violence against students with disabilities continues to occur in subtle and often unrecognized ways, affecting their psychological well-being and participation in learning. This phenomenon is driven by inequalities in social, cultural, and economic capital that shape unequal power relations within schools. This study aims to analyze the mechanisms of symbolic violence experienced by students with disabilities based on Pierre Bourdieu’s theory, particularly through the concepts of habitus, capital, and arena. The research employed a qualitative approach with a case study design. The participants included sixth-grade teachers and students, both with and without disabilities. Data were collected through observation, interviews, questionnaires, and documentation using instruments in the form of observation sheets, interview guidelines, and questionnaires based on the indicators of habitus, capital, and arena. Data were analyzed using the Miles and Huberman model, involving data reduction, data display, and conclusion drawing, with triangulation techniques to ensure validity. The findings reveal that symbolic violence operates subtly through the internalization of subordinative habitus, unequal access to capital, and school policies and practices that reproduce injustice. This study underscores the need for structural and cultural transformation in inclusive education to achieve authentic equity and encourages schools to reconstruct policies, instructional practices, and interactional cultures in more reflective and non-discriminatory ways.